Congenital fistula between left ventricle and coronary sinus. - McGarry, K M (1981)
The occurrence of a congenital fistula between the left ventricle and the coronary sinus has not previously been reported. A patient with this rare anomaly is described in whom the diagnosis was established during life and confirmed at operation and necropsy.